An Analysis Regarding the Association Between Connexins and Colorectal Cancer (CRC) Tumor Microenvironment - Liu YJ; Han M; Li JP; Zeng SH; Ye QW; Yin ZH; Liu SL; Zou X (Dove Medical Press, 2022)
Yuan-jie Liu,1,2,* Mei Han,1,* Jie-pin Li,1- 3 Shu-hong Zeng,1,2 Qian-wen Ye,1,2 Zhong-hua Yin,1,2 Shen-lin Liu,1,2 Xi Zou1,2,4 1Department of Oncology, Affiliated Hospital of Nanjing University of Chinese Medicine, Jiangsu Province Hospital of Chinese Medicine, Nanjing, People's Republic of China; 2No. 1 Clinical Medical College, Nanjing University of Chinese Medicine, Nanjing, People's Republic of China; 3Department of Oncology, Zhangjiagang TCM Hospital Affiliated to Nanjing University of Chinese Medicine, Zhangjiagang, People's Republic of China; 4Jiangsu Collaborative Innovation Center of Traditional Chinese Medicine in Prevention and Treatment of Tumor, Nanjing, People's Republic of China*These authors contributed equally to this workCorrespondence: Xi Zou; Shen-lin Liu, Email zxvery@126.com; lsljsszyy@126.comBackground: Gap junctions, as one of the major ways to maintain social connections between cells, are now considered as one of the potential regulators of tumor metastasis. However, to date, studies on the relationship between gap junctions and colorectal cancer (CRC) are limited.Methods: We synthesized connexins-coding gene expression data from public Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases. Bioinformatics analysis was performed using R software and several database resources such as MEXPRESS database, Gene Set Cancer Analysis (GSCA) database, Human Protein Atlas (HPA) database, Tumor Immune Single Cell Hub (TISCH) database, Search Tool for Retrieval of Gene Interaction Relationships (STRING), and Cytoscape software, etc., to investigate the biological mechanisms that may be involved in connexins. Immunofluorescence and immunohistochemical staining were used to validate the expression and localization of GJA4.Results: We found that CRC patients can be divided into two connexin clusters and that patients in cluster C1 had shorter survival than in cluster C2. The infiltration of M1 macrophages and NK cells was lower in cluster C1, while the levels of M2 macrophages and immune checkpoints were higher, indicating an immunosuppressed state in cluster C1. In addition, the epithelial-mesenchymal transition (EMT) phenotype was significantly activated in cluster C1. We observed that GJA4 was up-regulated in colorectal cancer tissues, which was related to poor prognosis. It was mainly expressed in fibroblasts, but the expression levels in normal intestinal epithelial cells were low. Finally, we found that GJA4 was associated with M2 macrophages and may be a potential immunosuppressive factor.Conclusion: We found that there is a significant correlation between abnormal connexins expression and patients' prognosis, and connexins play an important role in stromal-tumor interactions. Connexins, especially GJA4, can help enhance our understanding of tumor microenvironment (TME) and may guide more effective immunotherapeutic strategies.Keywords: colorectal cancer, gap junction protein alpha 4, cancer-associated fibroblasts, M2 macrophage, bioinformatics